2017
DOI: 10.3892/ol.2017.7672
|View full text |Cite
|
Sign up to set email alerts
|

Furin inhibitor D6R suppresses epithelial-mesenchymal transition in SW1990 and PaTu8988 cells via the Hippo-YAP signaling pathway

Abstract: Abstract. Hexa-D-arginine (D6R), an inhibitor of furin, has potential therapeutic applications in different types of human tumor. However, the function of D6R in targeting pancreatic cancer cells remains to be elucidated. In the present study, the proliferation, invasion and migration abilities of SW1990 and PaTu8988 cells were examined using a Cell Counting Kit-8, and Transwell and wound healing assays. Subsequently, the expression of proteins associated with epithelial-mesenchymal transition (EMT) and the Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Therefore, furin inhibitors can be used as a drug therapy for SARS-CoV-2 [41]. Patent literature since 1994 describes the use of furin or its inhibitors in the treatment of diseases, and some furin inhibitors that have been reported, including α-1-PDX (α1-antitrypsin Portland) [76], hexa-D-arginine(D6R) [77], serpin proteinase inhibitor 8 (PI8) [78], and a peptidomimetic furin inhibitor [79].…”
Section: Fusion Inhibitorsmentioning
confidence: 99%
“…Therefore, furin inhibitors can be used as a drug therapy for SARS-CoV-2 [41]. Patent literature since 1994 describes the use of furin or its inhibitors in the treatment of diseases, and some furin inhibitors that have been reported, including α-1-PDX (α1-antitrypsin Portland) [76], hexa-D-arginine(D6R) [77], serpin proteinase inhibitor 8 (PI8) [78], and a peptidomimetic furin inhibitor [79].…”
Section: Fusion Inhibitorsmentioning
confidence: 99%
“…Overexpression of YAP/TAZ has been found to induce EMT in various tumor cells, [122,123] while knockdown of YAP/TAZ can inhibit EMT. [124,125] Secondly, YAP promotes cell migration and invasion. For example, multiple studies have shown that knockdown or overexpression of LATS1/2 can promote or inhibit the migration and invasion of tumor cells, respectively.…”
Section: Tumor Metastasismentioning
confidence: 99%
“…It has been reported to suppress the concentration of processed S protein fragments, cytopathic effects, and viral production in SARS-CoV-2-infected VeroE6 cells, indicating furin inhibitor activity [ 67 , 68 ]. D6R, another furin inhibitor, is safer and therapeutically more effective than the other members of this class, but its effectiveness in SARS-CoV-2 infection is yet to be explored [ 69 ]. MI-1851 is another synthetic furin inhibitor that has been reported to suppress SARS-CoV-2 replication in Calu-3 human airway cells, leading to a 30- to 190-fold reduction in virus titers at a dose of 10 μM [ 70 , 71 ].…”
Section: Peptides As Drugs Against Covid-19mentioning
confidence: 99%